(untitled) (Damascus University Journal of agriculture sciences, 2021)
This research was carried out in the directorate of laboratories- ministry of Internal Trade and consumer protection and also the Department of Food Science - Faculty of Agriculture, Damascus University to determine antioxidant activity of ethanolic and oily extracts of Rosemary ( Rosmarinus officinalis). The extracts were added to soybean oil stored for 5 weeks in the oven at 65 °C and compared with the synthetic antioxidant (BHA). The antioxidant efficacy of ethanolic rosemary extracts with different concentrations (1000 and 2000 ppm) and oily extract 2% was estimated in accelerated oxidation conditions (Schaal oven test) by estimating peroxide value, free fatty acid% (Oleic acid) and total polar compounds. The results showed that Rosmary ethanolic extract with 2000 ppm had the highest antioxidant effect, while oily extract 2% had little effect on the protection of soybean oil from degradation during storage